Pro-inflammatory Cytokines, Endothelial Dysfunction and Hemocoagulation Disorders in Late-Stage Rheumatoid Arthritis with Antiphospholipid Syndrome - Yuliya A Sarycheva; Tatyana V Chernysheva (International Journal of Human and Health Sciences (IJHHS), 2026)
The activation of both cellular and humoral links of innate and acquired immunity with an imbalance between pro-inflammatory and anti-inflammatory cytokines can be observed at the various stages of the pathogenesis of rheumatoid arthritis. In some cases, dysregulation of the “cytokine cascade” leads to significant changes in the blood coagulation system, platelet activation, changes in the vascular wall, and the formation of blood clots in vessels of various sizes. The present study observed changes in the levels of interleukin-6, interleukin-18, and tumor necrosis factor -α and their effect on the main parameters of the hemostatic system and endothelial dysfunction in patients with late-stage of rheumatoid arthritis in condition of comorbidity with antiphospholipid syndrome. This cross-sectional study included 80 patients aged 40 to 65 years with a diagnosis of rheumatoid arthritis – 40 people with antiphospholipid syndrome and 40 without it. There was a direct correlation between increased levels of pro-inflammatory cytokines and an increase in platelet count, prothrombin index, fibrinogen, D-dimer, and endothelin-1; and an inverse correlation with values of activated partial thromboplastin time. It was found that an increase in the concentration of interleukin-6, interleukin-18 and tumor necrosis factor-α is associated with increased hypercoagulation, increased markers of endothelial dysfunction and thrombosis, which undoubtedly worsens the course of the underlying disease. International Journal of Human and Health Sciences Vol. 10 No. 04 Oct’26 Page: 283-287